2017
DOI: 10.1038/s41598-017-06617-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of clay minerals in Early Eocene volcanic paleosols on King George Island, Maritime Antarctica

Abstract: The paleoclimate during the Early Eocene in Maritime Antarctica is characterized by cool conditions without a pronounced dry season. Soils formed on volcanic material under such climate conditions in modern analogue environments are usually Andosols rich in nanocrystalline minerals without pedogenic smectite. The paleosols formed on volcanic material on King Georges Island are covered by basalts, dated by 6 new 40Ar/39Ar datings to 51–48 Ma, and are rich in smectite. A pedogenic origin of the smectites would s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…This basic guideline comes with the caveat that the clay mineralogy of the soil may reflect the composition of the source rocks for the sediment rather than the weathering conditions in the depositional basin (cf. Chamley, 1989;Chesworth et al, 2016;Evans, 1992;Spinola et al, 2017;Velde & Meunier, 2008). Thus, immature palaeosols, for example, Protosols, may inherit a substantial portion of their clay mineralogy from the source area due to the shorter period of residence for mineral grains in the A horizon, whereas mature palaeosols, in which the soil materials spend longer periods in the active soil layer, may better reflect climate conditions in the depositional basin.…”
Section: Palaeosols As a Record Of Palaeoclimatementioning
confidence: 99%
See 2 more Smart Citations
“…This basic guideline comes with the caveat that the clay mineralogy of the soil may reflect the composition of the source rocks for the sediment rather than the weathering conditions in the depositional basin (cf. Chamley, 1989;Chesworth et al, 2016;Evans, 1992;Spinola et al, 2017;Velde & Meunier, 2008). Thus, immature palaeosols, for example, Protosols, may inherit a substantial portion of their clay mineralogy from the source area due to the shorter period of residence for mineral grains in the A horizon, whereas mature palaeosols, in which the soil materials spend longer periods in the active soil layer, may better reflect climate conditions in the depositional basin.…”
Section: Palaeosols As a Record Of Palaeoclimatementioning
confidence: 99%
“…Nonetheless, a wide variety of palaeoclimate proxies have been utilised to quantify the timing and magnitude of the temperature changes in terrestrial environments leading up to and immediately following the boundary events. These include: leaf‐mass analysis and megafloral species richness, which have identified transient temperature spikes at and above the K–Pg boundary (Flynn & Peppe, 2019; Lyson et al, 2019; Wilf et al, 2003); analysis of leaf stomatal indices to track p CO 2 variations, which have suggested an intense p CO 2 spike at the boundary, but a strong decrease in the early Danian (Beerling et al, 2002; Steinthorsdottir et al, 2016); changes in palynomorph assemblages that demonstrate short warming events in the early Danian (Lyson et al, 2019); isotopic analysis of pedogenic carbonate, which suggest p CO 2 ‐driven temperature swings across the K–Pg boundary (Nordt et al, 2003; Zhang et al, 2018); and variations in clay mineral assemblages, such as the smectite/illite ratios in terrestrial depositional systems that record multiple warming and cooling episodes across the boundary (Gao et al, 2021). Unfortunately, most of these proxies rely on geological features with a discontinuous vertical distribution, unlike many of the proxies from the marine record, and are therefore unable to produce a high‐resolution palaeoclimate record.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural volcanic clay is abundant, simple, and cost-effective. Its chemical composition comprises silicon, alumina, magnesium, potassium, calcium, and iron [ [1] , [2] , [3] ]. Clay contains essential elements beneficial for healthcare and cosmetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on weathering in Antactica demonstrated the mineral alteration processes in soils (Ugolini & Anderson, 1973; Ugolini, 1976). Research on clay mineralogy in Maritime Antarctica is scarce and relatively new in comparison to other studies on soils in the region which have focused mainly on weathering patterns and the possible origins of these minerals (Jeong & Yoon, 2001; Lee et al ., 2004; Simas et al ., 2006; Mendonça et al ., 2013; Spinola et al ., 2017).…”
mentioning
confidence: 99%